Current Treatment of Filarial Cellulitis with Antibiotic Therapy-A Clinical Study - Shankar, Kakarparthy Ravi; Krupa, Mulla Divya (Indian Journal of Pharmacy Practice)
Background: Cellulitis is defined as an inflammation of skin and soft tissue associated with bacterial infection1 lower limbs are majorly effected area. Several studies and case reports support the safe usage of antibiotics for the effective treatment of cellulitis.2 Objectives: In this study, authors mainly concern about the positive outcomes of cellulitis treatment with various antibiotics. Results: Clinical symptoms are reduced within one week of antibiotic treatment and all these antibiotics are well tolerated and there were no severe side effects observed during the course of therapy. Conclusion: Results of the study indicates that antibiotics are effective in the treatment of cellulitis.
Keywords: Bullous Pemphigoid; Cellulitis; Lymphoedema; Mayalgia; Tenderness